Discovery and therapeutic potential of drugs that shift energy metabolism from mitochondrial respiration to glycolysis - Gohil, Vishal M. (2010)
Most cells can dynamically shift their relative reliance on glycolytic versus oxidative metabolism in response to nutrient availability, during development, and in disease. Studies in model systems have shown that re-directing energy metabolism from respiration to glycolysis can suppress oxidative damage and cell death in ischemic injury. At present we have a limited set of drugs that safely toggle energy metabolism in humans. Here, we introduce a quantitative, nutrient sensitized screening strategy that can identify such compounds based on their ability to selectively impair growth and viability of cells grown in galactose versus glucose. We identify several FDA approved agents never before linked to energy metabolism, including meclizine, which blunts cellular respiration via a mechanism distinct from canonical inhibitors. We further show that meclizine pretreatment confers cardioprotection and neuroprotection against ischemia-reperfusion injury in murine models. Nutrient-sensitized screening may offer a useful framework for understanding gene function and drug action within the context of energy metabolism.